Ira Aldridge : the vagabond years, 1833-1852 - Lindfors, Bernth (Rochester studies in African history and the diaspora, 2011)
Ira Aldridge: The Vagabond Years, 1833-1852 deals in depth with the later experiences of one of the modern world's first black classical actors as he toured throughout the United Kingdom impressing audiences with his virtuosity and versatility as an interpreter not only of tragic and comic black roles but also eventually as an actor of classic white Shakespearean parts -- Shylock, Macbeth, Richard III, even Iago. Aldridge was very popular in Ireland and remained there for six years, performing in venues large and small. He traveled often in his own carriage with assistants who supported him in scenes, enabling famous plays to be staged anywhere, even in villages that did not have a proper theater. He also performed periodically in large cities with professional acting companies, and returned to the London stage in 1848, after leaving it fifteen years earlier. During these years he expanded his repertoire, refined his skills, and gained a reputation as one of Britain's most talented thespians. In dealing with Aldridge's emergence as a professional actor in the United Kingdom, Lindfors here records in detail the ups and downs of his itinerant existence in a world where no theatergoer had ever seen anyone like him on stage before. Aldridge was genuinely a unique phenomenon in Britain at a pivotal point in history. Bernth Lindfors is Professor Emeritus of English and African Literatures, University of Texas at Austin, and editor of Ira Aldridge: The African Roscius (University of Rochester Press, 2007).